Adiabatic Fixed-Bed Gasification of Colombian Coffee Husk Using Air-Steam Blends for Partial Oxidation - Javier Bonilla; Gerardo Gordillo (Journal of Combustion)
The increasing energy consumption, mostly supplied by fossil fuels, has motivated the research and development of alternative fuel technologies to decrease the humanity’s dependence on fossil fuels, which leads to pollution of natural sources. Small-scale biomass gasification, using air-steam blends for partial oxidation, is a good alternative since biomass is a neutral carbon feedstock for sustainable energy generation. This research presents results obtained from an experimental study on coffee husk (CH) gasification, using air-steam blends for partial oxidation in a 10 kW fixed-bed gasifier. Parametric studies on equivalence ratio (ER) (1.53 < ER < 6.11) and steam-fuel (SF) ratio (0.23 < SF < 0.89) were carried out. The results show that increasing both SF and ER results in a syngas rich in CH4 and H2 but poor in CO. Also, decreased SF and ER decrease the peak temperature (Tpeak) at the gasifier combustion zone. The syngas high heating value (HHV) ranged from 3112 kJ/SATPm3 to 5085 kJ/SATPm3 and its maximum value was obtained at SF = 0.87 and ER = 4.09. The dry basis molar concentrations of the species, produced under those operating conditions (1.53 < ER < 6.11 and 0.23 < SF < 0.89), were between 1.12 and 4.1% for CH4, between 7.77 and 13.49% for CO, and between 7.54 and 19.07% for H2. Other species were in trace amount.